Enteric methane emissions from dairy systems in Kenya: A case study of Kenyan Rift Valley and Central Highlands regions - Mwema, Emmanuel; Steward, Peter; Gonzalez, Ricardo; Notenbaert, An (2025)
Kenya’s dairy sector contributes 12–14% of agricultural GDP but emits an estimated 12.3 Mt CO₂-eq annually, primarily from enteric methane. Reducing these emissions offers a significant mitigation opportunity. Improved feeding, especially through forages, can lower emission intensities while maintaining productivity. This study evaluated the mitigation potential of improved forages promoted by Venture37’s private sector-led alliance model, the Nourishing Prosperity Alliance (NPA), across seven counties using data from 834 dairy farmers in 2024 and 2025. Enteric methane emissions were quantified using an activity-detailed IPCC Tier 2 method, focusing on emissions per animal, per farm, and per kilogram of fat- and protein-corrected milk (FPCM). Results indicate that enteric CH₄ emissions increased with herd size, though most farms emitted less than 5 tons of CH₄ annually. Emission intensity consistently declined with higher milk yields, improved feed digestibility, and greater adoption of improved forages and supplements. Across both 2024 and 2025, a small group of low-efficiency farms accounted for a disproportionate share of mitigation potential, with total achievable savings of ~6.5 tons and ~6.2 tons of CH₄, respectively, while most farms required only modest milk yield gains to reach the top 10 efficiency benchmark. Farms with higher use of improved forages were consistently among the lowest methane-intensity producers, confirming feed quality as the dominant and most scalable mitigation lever in smallholder dairy systems